The Effectiveness of Cardiorehabilitation Programs in Returning to Work Post-CABG or PCI in Coronary Heart Disease - Darifah, Siti; Adi, Nuri Purwito; Widyahening, Indah Suci (Tirtayasa Medical Journal, 2022)
In developing countries, coronary heart disease (CHD) is one of the primary sources of disease burden. Cardiovascular rehabilitation is primarily used to help people recover after Coronary Artery Bypass Graft (CABG) or Percutaneous Coronary Intervention (PCI) and improve their quality of life, but still underutilized by public. The literature search was conducted in May 2018 through PubMed and Google Scholar using Boolean Operators. The search strategy used only articles in English from any years. The desired studies are randomized control trial, cohort, and systematic review. From one selected systematic review found that combined cardiac rehabilitation, physical conditioning with counseling and risk factor education, of cardiac rehabilitation programs are more effective than usual care. Combined cardiac rehabilitation programs may improve the rate of short-term return to work (RR 1.56, 95% CI 1.23-1.98; I2=20%; low certainty evidence). Combined cardiac rehabilitation probably reduce the average time needed to return to work (moderate-certainty evidence) by about 40 days when compared to receiving usual care. Combined cardiac rehabilitation is probably better than standar care in shorten rest time before return to work in post CABG or PCI patients